International Law and Dispute Resolution in the Context of Renewable Energy Development: A Review of the Case of Downstreaming of Nickel Ores by Indonesia - Nainggolan, Christian Imanuel (Faculty of Law, Universitas Negeri Semarang, 2023)
This paper delves into the intricate dynamics of international law and dispute resolution within the context of renewable energy development, focusing on Indonesia's downstreaming of nickel ores. As renewable energy initiatives gain prominence globally, the demand for essential minerals like nickel increases, prompting nations like Indonesia to explore downstreaming processes. However, this transition presents complex legal challenges, including international trade agreements, environmental regulations, and indigenous rights. Through a comprehensive review of relevant literature and case studies, this study analyzes Indonesia's approach to nickel ore downstreaming and its implications for international law and dispute resolution mechanisms. Additionally, it examines the role of international organizations, such as the World Trade Organization (WTO) and the United Nations Commission on International Trade Law (UNCITRAL), in resolving disputes arising from renewable energy projects. By synthesizing legal frameworks, environmental concerns, and socio-economic factors, this paper offers insights into navigating the legal complexities of renewable energy development, with a focus on Indonesia's nickel industry. Ultimately, the findings contribute to the discourse on sustainable resource management and the role of international law in facilitating equitable and environmentally responsible energy transitions.